Women in Trouble: Much Ado About Nothing, Pride & Prejudice and Bridget Jones’s Diary - Franziska Quabeck (European Journal of American Studies, 2024)
Shakespeare’s Beatrice, Jane Austen’s Lizzie Bennet and Helen Fielding’s Bridget Jones are three literary incarnations of the same female comic character. They share characteristics that make them all funny for the same reasons at vastly different times. This is due to an inextricable bond between gender and comedy that targets the audience’s expectations of normative femininity. The comic heroines in these three texts are all funny because they deliberately and consciously defy conventional constraints of femininity. The humor of each text results from the comic incongruity that is created by these women’s refusal to be what they ought to be and all three authors reward them for it.